EDUCATION AND ENTREPRENEURSHIP MOTIVATION: DO THEY INFLUENCE STUDENTS' ENTREPRENEURIAL INTEREST? - Endang, Endang (JURNAL EDUSCIENCE, 2024)
AbstrackThis research aims to determine the influence of entrepreneurship education and entrepreneurial motivation on the entrepreneurial interest of class X students at SMA Negeri 2 Pangkep. The variables in this research are entrepreneurship education as the independent variable (X1), entrepreneurial motivation as the independent variable (X2) and interest in entrepreneurship as the dependent variable (Y). The population of this study was all class X students of SMA Negeri 2 Pangkep. The sampling technique uses the Total Sampling technique, samples from the population are obtained from the entire population with a sample of 72 students. Data collection techniques are questionnaires and documentation. The data analysis techniques used are Descriptive Statistical Analysis, instrument testing, classical assumption testing and hypothesis testing.The results of this research show that: (1) based on the results of descriptive statistical analysis, entrepreneurship education of 73.93 percent is in the high category, entrepreneurship motivation of 73.65 percent is in the high category, and entrepreneurship interest is 76.70 percent in the high category. tall. (2) Based on the multiple linear regression analysis carried out, the multiple linear regression equation Y = 1.108 + 0.760X1 + 0.586X2 is obtained, which means that for each additional value of entrepreneurship education there will be an increase of 0.760 and entrepreneurial motivation will increase by 0.586. (3) Based on the results of the f-test, the value of the entrepreneurship education variable is 546.119 > 0.235 with a significance level of 0.000 < 0.05. (4) Based on the results of the coefficient of determination (R2) for entrepreneurship education, the value obtained is (R2) = 0.281 or 28 percent. Meanwhile, the results of the coefficient of determination (R2) for entrepreneurial motivation obtained a value of (R2) = 0.47 or 47 percent. From the results of the coefficient of determination (R2), this means that the influence of entrepreneurship education on interest in entrepreneurship is 28 percent, while the influence of entrepreneurial motivation on interest in entrepreneurship is 47 percent. The remaining 25 percent is influenced by other factors that have not been studied. (5) Based on the t-test on the entrepreneurship education variable, a t value of 7,207 was obtained with a significance level of 0.000 < 0.05 and entrepreneurial motivation was a t value of 5,460 with a significance level of 0.000 < 0.05. Because both variables have a significant value that is smaller than alpha, namely 0.05, the hypothesis has a positive and significant effect on interest in entrepreneurship.Keywords: Entrepreneurship Education, Entrepreneurial Motivation, Entrepreneurial Interest